2018
DOI: 10.1007/s42452-018-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

A review on environmental selenium issues

Abstract: Selenium is an essential element since it is necessary for metabolism and is also toxic to the living things if it is consumed above the desirable limit. For instance, up to 40 µg per d of dietary selenium is essential for human health; however, consumption of a little over 400 µg per d could result in adverse physiological problems. In the environment, selenium occurs in different species; of which selenate and selenite are its most toxic forms accounting for 95% of selenium toxicity. Though, selenium fortifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 95 publications
0
35
0
1
Order By: Relevance
“…In well or underground water, Se originates from both atmospheric deposits and soil drainage and, although in most cases it does not exceed 10 µg/L, Se levels may approach hundreds of µg/L as a consequence of increasing overuse of Se-based fertilizers [ 6 , 24 , 25 ]. Hence, in the last few decades, Se contamination in ground and surface water in numerous river basins worldwide has become a critical issue [ 26 ]. Moreover, concentration increases depending on pH as a result of conversion into compounds of greater solubility in water, such as selenites and selenates [ 27 ], which show a pro-oxidant action in the organisms and are considered very toxic in case of elevated intake [ 26 ].…”
Section: Selenium In the Environmentmentioning
confidence: 99%
“…In well or underground water, Se originates from both atmospheric deposits and soil drainage and, although in most cases it does not exceed 10 µg/L, Se levels may approach hundreds of µg/L as a consequence of increasing overuse of Se-based fertilizers [ 6 , 24 , 25 ]. Hence, in the last few decades, Se contamination in ground and surface water in numerous river basins worldwide has become a critical issue [ 26 ]. Moreover, concentration increases depending on pH as a result of conversion into compounds of greater solubility in water, such as selenites and selenates [ 27 ], which show a pro-oxidant action in the organisms and are considered very toxic in case of elevated intake [ 26 ].…”
Section: Selenium In the Environmentmentioning
confidence: 99%
“…The difference between first and second harvest was significant (P > 0.05) according to used statistical analyses (table 3), since the fortification did not take place after first harvest. Though, selenium fortification is important for normal human physiology in selenium deficient environments, it needs to be minimized or removed from selenium rich environmental media (Gebreeyessus and Zewge, 2019). Results indicated that the 50g/ha concentration of sodium selenate application in the form of foliar spray significantly enhanced the selenium content in garlic bulb (3.23±0.16mgSe/Kg) and vegetative part (15.46±0.71mgSe/Kg) where a 12.52 and 7.8 fold increase was observed respectively, as compared to control by Shafiq et al (2019).…”
Section: Selenium Contentmentioning
confidence: 99%
“…Selenium is biologically active at low concentrations for normal growth and development, and at moderate concentrations for homeostatic function (Hamilton, 2004). In human, low dietary selenium intakes are associated with health disorders including oxidative stress-related conditions, reduced fertility andimmune functions and an increased risk of cancers (Gebreeyessus and Zewge, 2019). Recommended appropriate dietary Se intake for healthy adult men is 80 μg day-1 and 55 μg day-1 for adult women, whereas a maximal daily safe dietary Se intake up to 400μg has been suggested for adults by WHO/IPCS (Ozkutlu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigations of selenium pollution, cycling, interaction, and biological treatment approaches have been reported in literature [23][24][25][26]. Wadgaonkar et al [27] reviewed the microbial transformation of selenium in soil and sediments and more recently, Getachew and Zewge [28] presented a scan of environmental issues caused by selenium.…”
Section: Introductionmentioning
confidence: 99%